Between Foreign and Family : Return Migration and Identity Construction among Korean Americans and Korean Chinese - Lee, Helene K., 1976- (Book collections on Project MUSE., 2018)
This book explores the impact of inconsistent rules of ethnic inclusion and exclusion on the economic and social lives of Korean Americans and Korean Chinese living in Seoul. Lee highlights the ""logics of transnationalism"" that shape the relationships between these return migrants and their employers, co-workers, friends, family, and the South Korean state.